Earthquake Trauma, Overgeneral Autobiographical Memory, and Depression Among Adolescent Survivors of the Wenchuan Earthquake - Tian, Qirui; Han, Han; Zhang, Dexiang; Ma, Yuanguang; Zhao, Jing; Li, Shouxin (Frontiers in Psychology, 2018)
Trauma has a profound impact on overgeneral autobiographical memory (OGM), which is a risk factor for depression. Violent earthquakes can cause tremendous trauma in survivors. We examined the relationship between earthquake trauma, OGM and depression in adolescent survivors of the Wenchuan earthquake in this study. OGM was assessed using the autobiographical memory test in a sample of adolescent participants who experienced the violent earthquakes in Wenchuan, China, in 2008 and control participants who had never experienced a destructive earthquake. Depression was measured using the Beck Depression Inventory-II in all participants. The results showed that compared with the adolescents with no earthquake trauma, the adolescents with earthquake trauma reported significantly more depression (d =.49) and overgeneral autobiographical memories (d =.55). Moreover, when they experienced earthquake trauma, the adolescents with low OGM did not experience more depression, but the adolescents with average and high OGM experienced more depression than the adolescents with no earthquake trauma. This finding indicated that in a non-Western cultural context, adolescents’ propensity toward OGM made them vulnerable to depression after experiencing an earthquake trauma.